Computational sensitivity evaluation of ultrasound neuromodulation resolution to brain tissue sound speed with robust beamforming - Boqiang Fan; Wayne Goodman; Sameer A. Sheth; Richard R. Bouchard; Behnaam Aazhang (Scientific Reports)
Abstract Low-intensity focused ultrasound (LIFU) neuromodulation requires precise targeting and high resolution enabled by phased array transducers and beamforming. However, focusing optimization usually relies on phantom measurements or simulations with inaccurate acoustic properties to degrade neuromodulation resolution. Therefore, this work analyzes the sensitivity of neuromodulation resolution, measured by off-target activation area (OTAA), to brain tissue sound speed. A Robust Optimal Resolution (ROR) beamforming method is proposed to minimize the worst-case OTAA with restricted sound speed inaccuracy and propagation information estimated with deviated sound speed. The propagation estimation model utilizes equivalent source method (ESM) to map sound field between different acoustic parameter sets. Simulation in a human head model validates the effectiveness of the proposed propagation estimation model, and shows that ROR beamforming method can significantly reduce the worst-case OTAA compared to benchmark methods by $$78.0 %$$ on average and up to $$90.0 %$$ , improving the robustness of stimulation and addressing the sensitivity issue. This allows reliable high-resolution neuromodulation in potential clinical applications with reduced invasive acquisition of propagation measurements for focusing optimization.